Sudden Onset of Diabetic Ketoacidosis in a Patient with Discordant HbA1C: A Unique Case of Fulminant Type 1 Diabetes Mellitus (FT1DM) in a Middle-aged Man - Nadine, I Gusti Ayu; Siregar, Jeremia Immanuel; Prasetya, Yonesha Rahmania (Medicinus, 2024)
Introduction: Diabetic Ketoacidosis (DKA) is an acute complication of diabetes mellitus (DM) which present as the first manifestation in fulminant type 1 diabetes mellitus (FT1DM) without significant elevation of HbA1C. We present a unique case of a 52-years-old male with DKA without previous history of DM and HbA1c of 6.6.Case Illustration: A 52-years-old male was brought to hospital due to persistent vomiting. He experienced polyuria and unexplained weight loss but denied previous history of DM. He was diagnosed with DKA due to his blood glucose of 1107 mg/dL along with elevated blood ketone and metabolic acidosis. However, his HbA1c was a mere 6.6. His serum lipase was increased, consistent with pancreatic damage. He was then discharged with basal-bolus insulin.  Discussion: Although the symptoms of this patient was consistent with hyperglycemic crisis, the presentation of DKA is usually associated with elevated HbA1c, approximately 10.4 - 16.9%. This unusual HbA1c points to the diagnosis of FT1DM. It is caused by sudden beta-cell destruction triggered by viral infections, alongside genetic disposition, leading to sudden depletion of insulin occurred less than a week and presents with ketoacidosis. It is characterized by low HbA1c (< 8.7%) yet extremely high blood glucose (≥ 288 mg/dl) and elevated pancreatic enzymes (depicting pancreatic damage). A diagnosis of FT1DM can be ascertained in this patient as his presentations matches its characteristics.Conclusion: FT1DM is a sub-type of T1DM which can suddenly occur in patients and associated with discordant HbA1c. It is important to recognize and treat it accordingly to avoid fatal outcomes.